High Pressure‐Driven Magnetic Disorder and Structural Transformation in Fe3GeTe2: Emergence of a Magnetic Quantum Critical Point. Issue 9 (25th January 2023) - Dang, Ngoc‐Toan; Kozlenko, Denis P.; Lis, Olga N.; Kichanov, Sergey E.; Lukin, Yevgenii V.; Golosova, Natalia O.; Savenko, Boris N.; Duong, Dinh‐Loc; Phan, The‐Long; Tran, Tuan‐Anh; Phan, Manh‐Huong
Abstract: Among the recently discovered 2D intrinsic van der Waals (vdW) magnets, Fe3 GeTe2 (FGT) has emerged as a strong candidate for spintronics applications, due to its high Curie temperature (130 – 220 K) and magnetic tunability in response to external stimuli (electrical field, light, strain). Theory predicts that the magnetism of FGT can be significantly modulated by an external strain. However, experimental evidence is needed to validate this prediction and understand the underlying mechanism of strain‐mediated vdW magnetism in this system. Here, the effects of pressure (0 – 20 GPa) are elucidated on the magnetic and structural properties of Fe3 GeTe2 by means of synchrotron Mössbauer source spectroscopy, X‐ray powder diffraction and Raman spectroscopy over a wide temperature range of 10 – 290 K. A strong suppression of ferromagnetic ordering is observed with increasing pressure, and a paramagnetic ground state emerges when pressure exceeds a critical value, P PM ≈ 15 GPa. The anomalous pressure dependence of structural parameters and vibrational modes is observed at P C ≈ 7 GPa and attributed to an isostructural phase transformation. Density functional theory calculations complement these experimental findings. This study highlights pressure as a driving force for magnetic quantum criticality in layered vdW magnetic systems. Abstract : Strong magnetic ordering suppression is discovered under high pressure, and a paramagnetic ground state emerges when pressure exceeds ≈15 GPa in Fe3 GeTe2 . An isostructural phase transformation occurs at ≈7 GPa. These findings highlight pressure as a driving force for magnetic quantum criticality in layered van der Waals (vdW) magnets like Fe3 GeTe2, rather than chemical doping that often induces structural disorder.